Caracterização física do solo e desempenho operacional de máquinas agrícolas na implantação da cultura do sorgo forrageiro - Lanca Rodrigues, Jose Guilherme; Fernandes, Jairo Costa; Nascimento, Flavia Meinicke; Gamero, Carlos Antonio [UNESP]; Bicudo, Silvio José [UNESP] (Universidade Estadual de Londrina (UEL), 2011)
Forage sorghum can be grown in areas presenting dry and hot environmental situations where the yield of other grasses can often be uneconomical. The objective of this study was to analyze the operating performance of agricultural machines in the deployment of sorghum forage in four tillage systems, as follows: no-tillage system, disk harrow + seeding, disk harrow + two light disking + seeding, minimum tillage + seeding and four seeding different speeds, as follows: 3, 5, 6 and 9 km h(-1). The study was performed under field conditions in FCA/UNESP, Botucatu County, SP, Brazil. The data were subjected to variance analysis in a simple factorial 4 x 4, and a random block design with split plots. Operational performance of the agricultural machinery, physical characteristics the soil, its water content and the yield of dry matter and green sorghum were determined. The operational performance of agricultural machines in the deployment of sorghum forage is influenced by the sowing speed and the soil tillage system used. Chisel plow was the equipment that required the highest mean traction force, mean traction and slip, as well as the lowest mean speed for the studied tillage system. Forage sorghum showed higher yields in no-tillage systems at a seeding speed of 5 km h(-1).
Physical characterization of soil and operational performance of agricultural machines in the deployment of forage sorghum
Keywords: Systems of soil tillage; speeding of sowing; soil physics